2018
DOI: 10.1371/journal.pone.0197133
|View full text |Cite
|
Sign up to set email alerts
|

Do altmetrics correlate with the quality of papers? A large-scale empirical study based on F1000Prime data

Abstract: In this study, we address the question whether (and to what extent, respectively) altmetrics are related to the scientific quality of papers (as measured by peer assessments). Only a few studies have previously investigated the relationship between altmetrics and assessments by peers. In the first step, we analyse the underlying dimensions of measurement for traditional metrics (citation counts) and altmetrics–by using principal component analysis (PCA) and factor analysis (FA). In the second step, we test the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 35 publications
5
86
0
5
Order By: Relevance
“…Our results demonstrate that there is no clear relation between citation metrics (used here as proxy for research quality) with social media and news media mentions, two proxies of societal impact via media. Similar results have been reported using Altmetric data in Bornmann and Haunschild 8 and in Jabaley et al 9 It can therefore be assumed that research quality itself is not sufficient for societal impact, which may be dependent on factors that could not be further explored in this study, such as active outreach to news media and social media by researchers or research institutes, and media culture.…”
Section: Discussionsupporting
confidence: 84%
“…Our results demonstrate that there is no clear relation between citation metrics (used here as proxy for research quality) with social media and news media mentions, two proxies of societal impact via media. Similar results have been reported using Altmetric data in Bornmann and Haunschild 8 and in Jabaley et al 9 It can therefore be assumed that research quality itself is not sufficient for societal impact, which may be dependent on factors that could not be further explored in this study, such as active outreach to news media and social media by researchers or research institutes, and media culture.…”
Section: Discussionsupporting
confidence: 84%
“…These measures can be used as an indication of attention to the publications. One of the problems with most altmetrics is currently that it is not clear what is measured (Bornmann & Haunschild, 2018a):…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to their expectations, their results suggested that F1000Prime rating scores as quality proxies of the papers played less of a role in the later citation counts than journal impact factor. Also, as a quality proxy, Bornmann and Haunschild (2018) found that the factor (citation and reader impact) was strongly correlated to paper quality using the negative binomial regression between F1000Prime scores and other citation-based metrics. They acknowledged the limitation of using F1000Prime data as a proxy for paper's quality.…”
Section: Literature Reviewmentioning
confidence: 99%